3D printing of earth-based materials: Processing aspects. (30th May 2018) - Perrot, A.; Rangeard, D.; Courteille, E.
Highlights: Using a fast setting binder, it is possible to print an earth-based mortar. Alginate is an efficient binder to enables earth printing. 3D printing can make an earth-based material with compressive strength in the same order of conventional cob earth. Young modulus and yield stress evolution of the material govern the maximum printing rate. Abstract: Due to its low environmental impact, earth construction has received much consideration in recent years. Nevertheless, its development remains limited due to low production rate. Recent developments have been made to improve earth-based materials mix-design and processing methods. Simultaneously, digitally based construction methods have been introduced in the field of construction especially for cement-based materials application. Among these new techniques, the so-called 3D printing by extrusion deposit has been the most intensively studied. In this study, we assess the possibility of adapting this technique to earth-based material. After making the earth's rheological behaviour suitable for 3D printing, a laboratory-scale printing has been carried out and the printed samples have been mechanically tested.